(untitled) (Journal of Universal Science Research, 2025)
In the modern world, teaching English requires more than traditional methods. The integration of 4C skills — Communication, Collaboration, Critical Thinking, and Creativity — is crucial for developing language learners who are competent, adaptive, and ready for future challenges. This paper explores how the 4C framework transforms English classrooms into interactive, engaging, and student-centered environments. It also discusses the benefits of applying the 4Cs in language teaching and offers practical strategies for implementation.